Genetic Incorporation of Multiple Unnatural Amino Acids into Proteins in Mammalian Cells1. Issue 52 (8th November 2013) - Xiao, Han; Chatterjee, Abhishek; Choi, Sei‐hyun; Bajjuri, Krishna M.; Sinha, Subhash C.; Schultz, Peter G.
<x xml:space="preserve">Abstract</x> An enhanced suppression system enables the expression of proteins in mammalian cells incorporating one unnatural amino acid (UAA) into multiple sites, as well as two different UAAs into distinct sites in a protein of interest. The utility of this technology was demonstrated by generating a full‐length antibody, site‐specifically conjugated to a drug and a fluorophore, and characterizing its activity in vitro (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>